Determining of Some Basin Characteristics Using Topographical Map and Digital Elevation Model 'A Case of Kazandere Stream Basin' - (:unkn) unknown (IOS PRESS, 2010)
In basin researches, quantitative data available from Topographical maps and Digital Elevation Model (DEM) make significant contributions to researchers in line with database created making use of Geographical Information Systems (GIS). Technological developments in the last 10 years, in particular, rendered GIS and Remote Sensing methods fit-for-use to achieve the objectives in geology-related applications. To identify applications of GIS in relation to basin researches, we selected the basin of the Kazandere Stream Basin of the castle located in Marmara Region as the field of study. In this study, we generated drainage network features of the basin using Arcinfo 9.2 GIS software from streams on 1/25000 scaled topographical map and from 10 m grid spaced DEM. We used Archydro Tool in line with the objectives of study. We obtained parameters in relation to stream directory analyses such as branching rate, drainage density and stream frequency of the field of study making use of topographical maps. And for DEM-related applications, we obtained information about subbasins by way of Flow Accumulation and Flow Direction model. DEM's are a general source of data for field analyses and 3-dimensional applications. Such basin characteristics as basin field, sub-basin fields, water running directions, drainage networks, catchment centreoid etc., are easily generated through DEM. Stream morphometric features found using such two data sources provide reliable information on drainage characteristics of the stream basin and its lower branches. Analyses and applications conducted within the framework of database created on GIS environment indicated that GIS could be used for multi-purposes under scope of geographical researches.
Keywords: Drainage Network; Kazandere Stream Basin; DEM; Topographical Map